Hepatocellular carcinoma in a case of hepatitis C - Suthar, Pokhraj P.; Parmar, Gaurav R.; Trivedi, Chinmay; Vithlani, Hemen I. (International Journal of Research in Medical Sciences, 2017)
Hepatocellular carcinoma has incidence of 90% of all liver cancers. HCC is the second most common hepatic malignancy in children after the hepatoblastomas. Patients with hepatocellular carcinoma presents with symptoms like pruritus, splenomegaly, bleeding oesophageal varices etc. Computed Tomography of the liver can look for local spread and thorax can look for metastases. Our case was a 49-year- old hepatitis C positive female came with vague right upper quadrant abdominal discomfort with weight loss of 7 lbs in last 2 months. Mild icterus was present on examination. CT scan revealed a well-defined iso-dense lesion in the segment V of right lobe of the liver, which shows enhancement in the hepatic arterial phase and rapid washout in the portal venous phase. Laboratory investigations showed abnormal liver function test. The HCV RNA levels were 1.45×105 IU/ml by real time PCR. Histopathology examination of biopsy specimen shows characteristic morphological features of steatohepatitic variant of hepatocellular carcinoma. Then the patient was referred to the higher center for the further management.